Evaluation of Pressure Ulcer Among the Critically Ill Patients Admitted in a Tertiary Hospital - Hossain, Bulbul; Mamun, Abdullah Al; Razi, Habib Al; Islam Raisul , Nurul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: All over the world pressure ulcer is a significant health care problem due to high morbidity and mortality rates and also high health care cost. This study was carried out with the objectives to identify the characteristics and associated factors of pressure ulcer among the critically ill patients admitted in a tertiary military hospital. Few studies have been conducted on pressure ulcer in Bangladesh and very few in military hospitals. Methodology: This was a cross sectional study conducted among purposively selected 53 critically ill admitted pressure ulcer patients in CMH Dhaka from 01 July 2018 to 31 December 2018 and data were collected by face to face interview and checklist. Results: Among the study population half (50.9%) were aged between 61-80 years with the mean age 69.13 years. The most common anatomical site of pressure ulcer were buttock (51.9%) followed by sacrum (38.5%) and 30.2% had multiple pressure ulcer. Among the critically ill patients, 81.1% had developed pressure ulcer after admission into hospital. The most common place of pressure ulcer was geriatric HDU (30.2%) and officers ward (18.9%). Among the pressure ulcer patients 79.2% were male. Most common stage of pressure ulcer were stage II (66.0%) followed by stage I (18.9%), stage III (13.2%) and stage IV (1.9%). All of them were bedridden and half (50.9%) were completely immobile. According to Braden Scale, about half (50.9%) had high risk for development of pressure ulcer followed by moderate risk (26.4%) and there were none beyond risk. About three fourth (73.6%) of pressure ulcer patients had hypertension & cerebrovascular diseases. Age group of 60-90 years, SSC & above educational group, male sex, immobility, low Braden score group patients are statistically significant (p < 0.05), and hypertensive and cerebrovascular diseased patients are not statically significant (p > 0.05) but having clear trends to be associate factors of pressure ulcer. Conclusion: The number of pressure ulcer were increasing with the increase of age. The higher age, male sex, immobilization, low Braden score, hypertension, and cerebrovascular diseased patients were more prone for development of pressure ulcer among the critically ill patients. J Bangladesh Coll Phys Surg 2022; 40: 23-30